Bond strengths of eight contemporary adhesives to enamel and to dentine: an in vitro study on bovine primary teeth - R. ATASH & A. VAN DEN ABBEELE (Paediatric Dentistry, 2005)
The aim of this study was to compare the shear and tensile bond strengths of eight adhesive systems to the enamel and dentine of primary bovine teeth.